Methodological quality of validation of studies on simulated scenarios in nursing - Juliana da Silva Garcia Nascimento; Fabiana Cristina Pires; Kleiton Gonçalves do Nascimento; Daniela da Silva Garcia Regino; Tainá Vilhar Siqueira; Maria Celia Barcellos Dalri (Universidade Federal do Ceará, 2021)
Objective: to evaluate the quality of the validation process performed in studies that developed simulated clinical scenarios for teaching and learning in nursing. Methods: the researchers conducted two steps: an integrative review in the Medical Literature Analysis and Retrieval System Online, Cumulative Index to Nursing and Allied Health Literature, Latin American and Caribbean Health Sciences Literature, Web of Science, SCOPUS, and Educational Resources Information Center databases; and the validation assessment, using the validated tool (Quality Assessment for Validity Studies). Results: 561 studies were identified, six of which comprised the sample, primary, methodological, available electronically and in full. Most showed good validation quality by meeting almost all the criteria required by the tool. Conclusion: the validation of studies on clinical scenarios was able to support reliable evidence for adoption in teaching through simulation in nursing.